Stabilisasi Tanah Gambut Dengan Menggunakan Campuran Kapur Studi Kasus : Ruas Jalan Rengat - Bukit Meranti Kecamatan Rengat Kabupaten Indragiri Hulu - Adel Yani; Hazanawati Hazanawati; Sahriyal Sahriyal (Jurnal Sipil Terapan, 2023)
Riau is one of three provinces with dominant peatlands. Indragiri Hulu Regency is the sixth largest district with the largest area of ​​peatland with a value of 222 thousand hectares. Particularly in Sekip Hilir Village, Rengat District, Indragiri Hulu Regency, there is quite extensive peatland and in this location there is infrastructure in the form of Jalan Rengat – Bukit Meranti. The construction of road infrastructure on peatlands has experienced many problems. This is because peat soil has a very low carrying capacity so that the settlement that occurs is large and unable to support the work load. Stabilization efforts are needed to improve the carrying capacity of peat soils. Stabilization on peat soil will be carried out chemically using lime as a stabilizing mixture with variations of 5%, 10% and 15%. From the results of the tests carried out, namely the addition of lime variations to the peat soil stabilization mixture is proven to increase the CBR (California Bearing Ratio) value. The CBR value of peat soil mixture with the addition of 5% lime was obtained at 17.28%. At the addition of 10% lime the CBR value increased to 21.81% and at the addition of 15% lime it increased to 30.04%. From the CBR value of peat soil with variations in lime mixture obtained, the authors prove that an addition of ≥ 5% has been able to achieve a laboratory CBR standard value of 17.28% and has met the Bina Marga specifications for road pavement subgrade, namely ≥ 6%. .